A strategy to improve the adsorption capacity of OPs-dye pollutants from the aqueous environment using adsorbents based on 2D transition metal carbides (V2CTx) - Ali Bina; Heidar Raissi (Applied Water Science)
Abstract Remediation of water pollution or removal of pollutant molecules by efficient substrates with long life is very important and challenging. Techniques based on adsorption and extensive use of two-dimensional (2D) transition metal carbides (MXenes) with the presence of terminal functional groups have provided a high potential in the separation of organic aromatic pollutants. In this work, a 2D substrate of the MXenes family named V2CTx is designed to investigate the adsorption behavior of several types of dye organic pollutants using the molecular dynamics simulation technique based on Newton’s laws in the aqueous phase. Several simulation boxes are designed, which are placed in two groups, discrete simulation boxes and co-loading (Mxn-Mix) boxes. Several analyses, including root-mean-square deviation, interaction energies, radial distribution function, mean square displacement, hydrogen bond (HB) number, and the number of contacts, have been used to analyze the results. The simulation results and interaction energy show that all the dye analytes used can interact with MXene (Mxn), which indicates that MXene can be an effective adsorbent to remove pollutant molecules. Our results confirm that the adsorption process of analytes by V2CTx substrate is selective. The analysis of adsorption behavior shows that the loading process is spontaneous in all systems, and the values of the interaction energy for the most stable complexes are −149.95 and −104.85 kJ/mol corresponding to crystal violet and brilliants blue analytes, respectively, in both groups of discrete and Mxn-Mix simulation boxes. The strong adsorption can be attributed to the cationic nature of analytes and their nucleophilic aromatic parts, which caused strong coul interactions for the adsorption of these molecules. The HB and π–π interactions are also responsible for the adsorption of dye molecules here. The obtained results also indicate that in addition to the cationic nature, other factors, such as the linearity of the molecular structures, the charge of the dye molecules, and the molecular mass of the tested pollutants, are effective in the adsorption process. Current studies show that the Mxn nanostructure is an excellent substrate of adsorbent material that has high efficiency for the separation of organic dyes in aqueous media. It is hoped that this research can be a very good class for other target pollutants in the future.